Phytochemical analysis, digestive enzymes inhibition, and toxicity study of Beta vulgaris (BIBECHANA, 2024)
Beta vulgaris is an annual crop grown for its edible roots and leaves. It is traditionally used for the treatment of diabetes, cancer, obesity, heart problems, kidney problems, and liver diseases. The present work is centered on the phytochemical analysis and assessment of antioxidant, antimicrobial, and antidiabetic activities, and toxicity in the root and leaf extracts and solvent fractions. TPC and TFC were measured using the Folin-Ciocalteu phenol reagent method and AlCl3 colorimetric method respectively. Antioxidant and antidiabetic activity were measured with DPPH assay and α-glucosidase enzyme inhibition assay. Antimicrobial activity was determined with the agar disc diffusion method and brine shrimp assay was performed to measure toxicity. Phytochemical analysis revealed the presence of phenols, flavonoids, glycosides, saponins, tannins, terpenoids, and alkaloids. The ethyl acetate fraction of the root contained the highest amount of phenolics with 84.35 ± 0.94 mg GAE/g. Total flavonoid content was found highest in the hexane fraction of root at 150.48 ± 1.10 mg QE/g. The ethyl acetate fraction of the root displayed an IC50 of 3.92 ± 0.06 µg/mL in the DPPH assay. The plant extracts and fractions possessed weak α-glucosidase enzyme inhibition activity. They were inactive against bacterial species of Escherichia coli, Bacillus subtilis, Staphylococcus aureus, Klebsiella pneumoniae, and fungal species of Fusarium solani. Toxicity assay found the plant to be non-toxic against the brine shrimp nauplii with the lowest LC50 value being 1166.36 ± 100.21 µg/mL for the hexane fraction of leaf. The study finds B. vulgaris to be rich in phytochemicals and antioxidant activity with weak α-glucosidase enzyme inhibition activity. It is non-toxic to brine shrimp larvae.